The Effect of Altman Z-Score as Tool for Predicting Potential Bankruptcy on Stock Prices in Retail Subsector Companies Listed on the IDX in 2019 – 2021 - IGA Kade Amanda Githayoni; Cening Ardina; I Made Wijana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The purpose of this study is to determine the Effect of Altman Z-Score as Tool for Predicting Potential Bankruptcy on Stock Prices in Retail Companies Listed on the IDX in 2019 – 2021. The data collection technique in this study uses documentation methods as well as literature studies published by the company. The data in this study uses financial statements published by retail sector companies listed on the Indonesia Stock Exchange in 2019 – 2021 by sampling using purposive sampling techniques. Companies that have met the sampling criteria are 11 companies. The data analysis method in this study uses Altman Z-score bankruptcy analysis, as well as for financial ratios using the ratio of Altman Z- score consisting of Working capital on total assets, retained earnings on total assets, profit before tax and interest on total assets, and book value of total equity at the book value of total liabilities. The next data analysis technique in this study used classical assumption tests, simple liner regression, and other hypothesis test tools. The results of this study showed that the Altman Z-score had a significant effect on the Stock Price of 17.7% with a calculated t value of 2.578 > 2.03951 (0.05 significant α) from the table. Based on the results of the Calculated Altman Z-score classification, it is shown that in 2021 there are 36 companies in a state of bankruptcy, 28% are in a state of gray area, and 36% are in a safe state.